2013
DOI: 10.1371/journal.pone.0063442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Signal Peptide on Stability and Folding of Escherichia coli Thioredoxin

Abstract: The signal peptide plays a key role in targeting and membrane insertion of secretory and membrane proteins in both prokaryotes and eukaryotes. In E. coli, recombinant proteins can be targeted to the periplasmic space by fusing naturally occurring signal sequences to their N-terminus. The model protein thioredoxin was fused at its N-terminus with malE and pelB signal sequences. While WT and the pelB fusion are soluble when expressed, the malE fusion was targeted to inclusion bodies and was refolded in vitro to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 61 publications
1
47
0
Order By: Relevance
“…These results indicated that the native signal sequence of Est1 interfered with correct protein folding, when not cleaved correctly during secretion. Similar observations for E. coli were made previously [25].…”
Section: Fig 1 (A) Expression Of Est1 With E Coli Bl21 (De3)star Pesupporting
confidence: 89%
“…These results indicated that the native signal sequence of Est1 interfered with correct protein folding, when not cleaved correctly during secretion. Similar observations for E. coli were made previously [25].…”
Section: Fig 1 (A) Expression Of Est1 With E Coli Bl21 (De3)star Pesupporting
confidence: 89%
“…17 Secretory proteins such as CCL11 only become functional after crossing the membrane and arriving to the appropriate cellular compartment and, consequently, being cleaved by signal peptidases. 49,50 The signal peptide plays important roles in targeting and membrane insertion, and after being cleaved can also exert other functions such as protecting cells from being killed by other cells. [49][50][51][52] Before cleavage, the signal peptide may have also important functions in protein folding and maturation.…”
Section: Resultsmentioning
confidence: 99%
“…49,50 The signal peptide plays important roles in targeting and membrane insertion, and after being cleaved can also exert other functions such as protecting cells from being killed by other cells. [49][50][51][52] Before cleavage, the signal peptide may have also important functions in protein folding and maturation. 52 Therefore, mutations in the signal peptide may interfere with such functions.…”
Section: Resultsmentioning
confidence: 99%
“…S3 in the supplemental material). The mechanism of protein secretion in eukaryotes and prokaryotes requires the signal sequence to facilitate transport of the translated protein to the membrane (31), and it also helps the protein attain the right conformation required to maintain its functionality (32). The fact that the major sequence difference between the FAD-I of ATCC 10953 and those of the other two strains is in the signal peptide domain of FAD-I ( Fig.…”
Section: Discussionmentioning
confidence: 99%